ANALISIS NILAI GIZI DAN TINGKAT PENERIMAAN KONSUMEN TERHADAP FORMULA BISCUIT TEPUNG IKAN PAYANGKA(OPHIELEOTRIS APOROS) - Ana B. Montol; Nita R. Momongan; I Made Djendra (POLTEKKES KEMENKES MANADO, 2016)
Period toddler requires serious attention, especially in the fulfillment of basicrights such as child care and the provision of nutritious food. This requires the availabilityof various types of food-grade toddler, has a high nutritional value and can be acceptedor liked toddlers. Children need to be given extra food to ensure the occurrence of weightgain and optimal brain development.In addition Payangka fish flour (Ophieleotris aporos) have a high protein, thequality of protein is also almost perfect approach the equivalent of egg protein, thepayangka fish flour very well to serve as a source of animal protein in the manufacture ofinfant formula foods (biscuits). This study aimed to: develop a formula biscuits with localfood ie payangka (Ophieleotris aporos) fish flour as a source of protein, knowing thenutritional value and the level of consumer preferences of the formula payangka(Ophieleotris aporos) fish flour biscuits.This study uses a completely randomized design with empart treatments and fourreplications. To determine the level of consumer acceptance of organoleptic testingpayangka fish flour biscuit formulation conducted using somewhat trained panelists asmany as 50 people. Proximate analysis was conducted to determine the nutritional valueof payangka fish flour biscuit formula most preferred form of carbohydrate, protein, fatand ash content.The research was conducted in two stages. First step is the manufactureof payangka fish flour then the second stage of the manufacture of payangka fish flourbiscuits followed by organoleptic testing and analysis of nutritional biscuits most preferredformula. The results showed the level of acceptance of the panelists on the color ofbiscuits, 44% like in the sample F1, 56% like in the samples F2 and 36% somewhat likethe F3 sample. The acceptance rate of the aroma biscuit panelists showed 56% like inthe sample F1, 52% like the 34% sample F2 and F3 like in the sample. A level of thesense of biscuits showed 52% like in the sample F1, 42% are very fond of sampling F2and 34% somewhat like the F3 sample. A level of the texture of the biscuits showed only16% are very fond of F1 sample, 34% are very fond of sampling F2 and 42% are veryfond of F3 samples. F1 overall sample had a mean score of 3.87 hedonic, F2 sample hada mean score of hedonic 4:05 and F3 samples had a mean score of hedonic 3.85. Thusthe sample F2 is formula biscuit with substitution of payangka fish flour biscuit 20% ishighly preferred by the panelists. Results of the proximate analysis showed payangka fishflour biscuits 20% contains protein29.35%, 16:41% fat, karbihidrat 50.68% and ashcontent 1:29%.